2017
DOI: 10.1002/cbin.10803
|View full text |Cite|
|
Sign up to set email alerts
|

ox‐LDL increases microRNA‐29a transcription through upregulating YY1 and STAT1 in macrophages

Abstract: Macrophages and oxidized low-density lipoprotein (ox-LDL) have been verified playing vital roles in the pathogenesis of atherosclerosis (AS). Previous studies demonstrated that microRNA-29a (miR-29a) was upregulated in many atherogenic process and cells, thus acting as an important participant in AS. But the detailed regulation mechanism of miR-29a in AS has not been fully understood. In our study, we demonstrated a positive feedback loop of ox-LDL-SRA-miR-29a. Furthermore, we found that YY1 and STAT1 were upr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Previous studies have indicated that the PI3K/AKT/mTOR signaling pathway plays a critical regulatory role in autophagy [ 11 ]. We investigated the specific effects of miR-29a on autophagy and PI3K/AKT/mTOR signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have indicated that the PI3K/AKT/mTOR signaling pathway plays a critical regulatory role in autophagy [ 11 ]. We investigated the specific effects of miR-29a on autophagy and PI3K/AKT/mTOR signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, many studies have reported the inseparable relationship between miRNAs and AS, which are involved in the functional regulation of mononuclear macrophages [8][9][10]. In addition, Jian et al have confirmed that miR-29a could promote the secretion of pro-inflammation factors such as interleukin-1 (IL-1), IL-6, and TNF-α and affect the formation of atherosclerotic plaques by regulating the survival status of macrophages [11]. However, the underlying molecular mechanisms of miR-29a in AS are not fully clear.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, YY1 initiated the activity of the X-inactive specific transcript (Xist) promoter by directly binding to the Xist 5' region in ES cells ( 24 ). Downstream, YY1 was also revealed to be involved in the pathophysiology of AS by regulating cell proliferation and apoptosis ( 12 , 26 , 27 ). For example, a previous study reported that YY1 was involved in the promoting effects of miR-544 on the maturation and antioxidative effects of stem cell-derived endothelial-like cells ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a previous study reported that YY1 was involved in the promoting effects of miR-544 on the maturation and antioxidative effects of stem cell-derived endothelial-like cells ( 28 ). A previous mechanistic analysis of YY1 in ox-LDL-treated macrophages of AS demonstrated that YY1 can translocate into the nucleus and increase the expression of miR-29a by binding to its transcriptional promoter region ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Western blot and qPCR assay were performed as described previously . Oligo(dT) primers were used as follows: IFI35: 5′‐AACAAAAGGAGCACACGATCA‐3′ and 3‐′CTCCGTTCCTAGTCTTGCCAA‐5′; P65: 5′‐ATGTGGAGATCATTGAGCAGC‐3′ and 3′‐CCTGGTCCTGTGTAGCCATT‐5′; GAPDH: 5′‐TCAACGACCACTTTGTCAAGCTCA‐3′ and 3′‐GCTGGTGGTCCAGGGGTCTTACT‐5′.…”
Section: Methodsmentioning
confidence: 99%